Inkontinensia Urin pada Lansia: Analisis Sosiodemografi Dampak Latihan Kegel Terhadap Kualitas Hidup Lansia - Nungki Marlian Yuliadarwati; Himawan Wismanadi; Noortje Anita Kumaat (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Urinary incontinence is a common health issue among the elderly, particularly women (approximately 77% of cases), influenced by physiological factors such as pelvic floor muscle weakness due to menopause, a history of multiple pregnancies, and comorbid conditions like hypertension (38%), osteoarthritis (31%), and diabetes (20%). The prevalence of this condition increases the risk of social isolation and declines in quality of life, while low physical activity (light to moderate) worsens the condition due to sarcopenia and balance impairments. This study explores risk factors and the effectiveness of non-invasive interventions such as Kegel exercises for prevention and rehabilitation. To identify risk factors for urinary incontinence (UI) in elderly women, including pregnancy history, chronic diseases, and physical activity levels, and to analyze the physiological impact of multiple pregnancies on pelvic floor muscles in elderly women at Puskesmas Pandanwangi, Malang, Indonesia, as well as the relationship between these factors and UI. This study employed a quasi-experimental pre- and post-test one-group design involving 65 elderly participants, data collected simultaneously to provide a snapshot of their current condition. The dependent variables were quality of life in elderly individuals with incontinence, measured using the ICIQ-SF (International Consultation on Incontinence Questionnaire) and the 3IQ (Three Incontinence Questionnaire). Data analysis was performed using the Wilcoxon signed-rank test with the assistance of SPSS 26. The findings indicate a significant effect (p-value = 0.000) of Kegel training on the quality of life among elderly individuals with incontinence, restoring anatomical and physiological function of the urogenital system, strengthening neuromuscular control, promoting physical mobility and freedom, and stimulating improvements in mental health and overall quality of life. Kegel exercises are a safe, effective, low-cost intervention that not only addresses urinary incontinence but also serves as a foundation for holistic elderly well-being Keywords: Urinary Incontinence, Kegel Exercises, Elderly, Incontinence.  ABSTRAK Inkontinensia urin merupakan masalah kesehatan umum pada lansia, terutama perempuan (sekitar 77% kasus), yang dipengaruhi oleh faktor fisiologis seperti pelemahan otot dasar panggul akibat menopause, riwayat kehamilan berulang, dan penyakit penyerta seperti hipertensi (38%), osteoarthritis (31%), serta diabetes (20%). Prevalensi ini meningkatkan risiko isolasi sosial dan penurunan kualitas hidup, sementara aktivitas fisik rendah (ringan/sedang) memperburuk kondisi karena sarkopenia dan gangguan keseimbangan. Penelitian ini mengeksplorasi faktor risiko dan efektivitas intervensi non-invasif seperti latihan Kegel untuk pencegahan dan rehabilitasi. Mengidentifikasi faktor risiko UI pada lansia perempuan, termasuk riwayat kehamilan, penyakit kronis, dan tingkat aktivitas fisik dan Menganalisis dampak fisiologis kehamilan berulang terhadap otot panggul lansia di puskesmas pandanwangi Mota Malang dan hubungannya dengan UI lansia di Puskesmas pandan wangi Kota Malang. Jenis penelitian ini menggunakan quasi eksperimnta jenis pre dan post test one grup design sebanyak 65 lansia, dikumpulkan dalam waktu yang bersamaan untuk memberikan gambaran kondisi saat itu. Variabel dependen yang digunakan dalam penelitian ini adalah derajat kualitas hidup pada lansia dengan inkontinensia menggunakan ICIQ-SF (International Consultation on Incontinence Questionnaire) dan mengukur evaluasi dari inkontinensia 3IQ (Three Incontinence Questionnaire). Analisis data menggunakan wilcoxon dengan bantuan SPSS 26. Hasil penelitian menunjukkan bahwa terdapat pengaruh signifikan p valiu (0.000) dampak latihan kegel terhadap kualitas hidup lansia dengan mengembalikan fungsi anatomi dan fisiologi dari sistem urogenital, memperkuat kontrol saraf-otot, mendorong mobilitas dan kebebasan fisik, dan Memicu perbaikan kesehatan mental dan kualitas hidup lansia. Kata Kunci: Inkontinensia Urin, Latihan Kegel, Lanjut Usia, Mengompol.